Examining the Effect of Extracurricular Activities on Academic Achievements among the Public University Students in Malaysia - Sayed Kushairi, Sayed Nordin (Canadian Center of Science and Education, 2014)
The objective of this study is to examine how physical, educational, and social extracurricular activities affect academic achievements of the participating students in Peninsular Malaysia. A cross-sectional design and quantitative method is applied, and complete data is collected from 150 students from three public universities in Peninsular Malaysia. Findings of this study indicate that there is no significant positive association between participation in extracurricular activities and student’s academic achievements. These alarming findings suggest that, besides emphasizing on promoting extracurricular activities to improve students’ knowledge and understanding, both universities and policy makers should be more aware of designing effective extracurricular activities and should establish a standard framework for continuous assessments of the outcome of these activities.